Community Participation Level in Development of Keseneng Tourism Village - Safii, Adnan Abdul; Pujiati, Amin (Universitas Negeri Semarang, 2019)
This research aims to identify the level of community participation in the development of Keseneng Tourism Village, to know the inhibiting factors in the development of tourism villages, and to identify efforts to overcome obstacles to increase the participation of the Keseneng Village community. The design in this study is a case study research with a type of qualitative descriptive research. The data used are primary and secondary data. Data collection techniques used are observation, interviews and documentation. The data validity technique uses triangulation techniques. Trianggulation technique means using different data collection techniques to get data from the same source. The results showed that the level of community participation in the development of the Keseneng Tourism Village using the Arnstein ladder was in the stage of Placatation. Participation in the threatening stage means that the communication made by the community and the government has been done well. The community also has the opportunity to place its representatives in the development of Keseneng Tourism Village activities. The inhibiting factors in the development of Keseneng Tourism Village are lack of funding, quality of Human Resources, knowledge and insights of the community regarding tourism villages, and incomplete facilities and infrastructure. Efforts are being made to overcome obstacles by disseminating tourism, providing skills training, fostering tourism villages, participating in marketing and publishing Keseneng Tourism Village, as well as comparative studies to other tourist villages. Penelitian ini bertujuan untuk mengidentifikasi tingkat partisipasi masyarakat dalam pengembangan Desa Wisata Keseneng, mengetahui faktor penghambat dalam pengembangan desa wisata, serta mengetahui upaya dalam mengatasi hambatan untuk meningkatkan partisipasi masyarakat Desa Keseneng. Desain dalam penelitian ini adalah penelitian studi kasus dengan jenis penelitian deskriptif kualitatif. Data yang digunakan adalah data primer dan sekunder. Teknik pengumpulan data yang digunakan adalah observasi, wawancara serta dokumentasi. Teknik keabsahan data menggunakan trianggulasi teknik. Hasil penelitian menunjukkan bahwa tingkat partisipasi masyarakat pengembangan Desa Wisata Keseneng menggunakan tangga Arnstein berada pada tahap Penentraman (Placatation). Partisipasi tahap Penetraman berarti bahwa komunikasi yang dilakukan masyarakat dan pemerintah telah dilakukan dengan baik. Masyarakat juga memiliki kesempatan untuk menempatkan perwakilannya dalam kegiatan pengembangan Desa Wisata Keseneng. Faktor penghambat dalam pengembangan Desa Wisata Keseneng yaitu kurangnya pendanaan, kualitas Sumber Daya Manusia, pengetahuan dan wawasan masyarakat mengenai desa wisata, serta sarana dan prasarana belum lengkap. Upaya yang dilakukan masyarakat dan pemerintah untuk mengatasi hambatan dengan melakukan sosialisasi kepariwisataan, memberikan pelatihan keterampilan, pembinaan desa wisata, ikut memasarkan dan mempublikasikan Desa Wisata Keseneng, serta studi banding ke desa wisata lain.